1991
DOI: 10.1002/jemt.1060190103
|View full text |Cite
|
Sign up to set email alerts
|

Fetal development and regulation of pituitary cell types

Abstract: The ontogenesis of the pituitary gland is considered from anatomical and functional points of view. Embryogenesis of the hypothalamo-pituitary unit involving development of the hypothalamo-hypophyseal portal system is complete during early life as shown in several mammalian species. The ultrastructural characteristics of the different cell types during development are described according to observations made by using immunochemical techniques. The patterns of differentiation of the cell types are reviewed acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 159 publications
(172 reference statements)
0
13
0
Order By: Relevance
“…However, the spe cific mechanisms and tissue interactions underlying this commitment are still unknown. An important role of the hypothalamus in the development of the adenohypophy sis has been suggested in several species such as chick [22][23][24][25][26], urodele [27], anuran [28], and rat [6,[29][30][31]. How ever, it should be noted that these studies have been per formed at later stages, when Rathke's pouch has already taken place.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the spe cific mechanisms and tissue interactions underlying this commitment are still unknown. An important role of the hypothalamus in the development of the adenohypophy sis has been suggested in several species such as chick [22][23][24][25][26], urodele [27], anuran [28], and rat [6,[29][30][31]. How ever, it should be noted that these studies have been per formed at later stages, when Rathke's pouch has already taken place.…”
Section: Discussionmentioning
confidence: 99%
“…in ref. 6], However, whether the pre sumptive territory of nasal cavity ectoderm and/or that of the hypothalamus participate in the commitment of the adenohypophysis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decreased levels of maternal plasma corticosterone (Cort) by maternal adrenalectomy also result in reduced birth weight, and very low levels of Cort are sufficient to normalize birth weight and increase fetal Cort levels (51). As fetal adrenals start functioning during the last week of gestation (16), maternal glucocorticoid levels are the primary regulators of fetal development during the first 2 wk of gestation. Subsequently, maternal Cort might affect fetal development indirectly through regulating fetal adrenal function during the last week of gestation.…”
mentioning
confidence: 99%
“…It has been suggested that they also are important for the differentiation of the various cell types of the adenohypophysis [4], Several transcription-activat ing proteins have been implicated in the definition of ade nohypophysial cell phenotypes: Pit-1, a homeobox pro tein, is selectively expressed in cells responsible for growth hormone (GH), prolactin (PRL) and (i-thyrotropin ((3-TSH) synthesis [5], is expressed during gestation immediately prior to the onset of these hormones [6][7][8] and is necessary for the differentiation of these cells [9], The nuclear receptor steroidogenic factor-1 (SF-1), a member of the steroid receptor superfamily [10,11], is necessary for the differentiation of pituitary gonadotropes [12]. Anencephalic fetuses provide an excellent model to study the development of adenohypophysial cells in the absence of hypothalamic regulation; despite the absence of a hypothalamus, anencephalic fetuses develop pituitaries composed of adenohypophysial cells [13,14].…”
Section: Introductionmentioning
confidence: 99%